2019
DOI: 10.3389/frobt.2019.00117
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Trust in Automated Vehicles: Role of Traffic Signal and AV Driving Behavior

Abstract: Pedestrians' acceptance of automated vehicles (AVs) depends on their trust in the AVs. We developed a model of pedestrians' trust in AVs based on AV driving behavior and traffic signal presence. To empirically verify this model, we conducted a human-subject study with 30 participants in a virtual reality environment. The study manipulated two factors: AV driving behavior (defensive, normal, and aggressive) and the crosswalk type (signalized and unsignalized crossing). Results indicate that pedestrians' trust i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 65 publications
4
50
0
Order By: Relevance
“…For many, aging can correspond with greater difficulty in driving, and according to the US Census Bureau, approximately 70 million individuals in the United States will be over the age of 64 by 2030 ( Figure 1) [4]. This explains why AVs are suggested as one potential solution, but a lack of trust hinders that adoption across all age groups [5,6]. The Society of Automotive Engineers (SAE) classifies driving automation into six levels ranging from 0 to 5, as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…For many, aging can correspond with greater difficulty in driving, and according to the US Census Bureau, approximately 70 million individuals in the United States will be over the age of 64 by 2030 ( Figure 1) [4]. This explains why AVs are suggested as one potential solution, but a lack of trust hinders that adoption across all age groups [5,6]. The Society of Automotive Engineers (SAE) classifies driving automation into six levels ranging from 0 to 5, as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…For model training and testing, we isolated scenes that had at least one AV interacting with the pedestrian. More details about the data collection methodology and the user study can be found in [17], [65].…”
Section: A Datasetsmentioning
confidence: 99%
“…Reig et al [64] studied pedestrian trust in autonomous vehicles via interviews, showing for example that participants who were favourable to AVs were more likely to trust them and that the lack of knowledge about AV technology leads to mistrust. Using the definition of trust in [46] introduced above, Jayaraman et al [38] studied pedestrians' trust in autonomous vehicles in a VR experiment followed by a questionnaire using a Likert scale. It is argued that human trust increases with the increase of available information, and found that the AV's driving behaviour and the presence of light can influence the trust of pedestrians.…”
Section: Trust In Human-av Interactionsmentioning
confidence: 99%